2016
DOI: 10.1161/circoutcomes.116.002714
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Physician Teamwork and Health System Outcomes After Coronary Artery Bypass Grafting

Abstract: Background-Patients undergoing coronary artery bypass grafting (CABG) must often see multiple providers dispersed across many care locations. To test whether teamwork (assessed with the bipartite clustering coefficient) among these physicians is a determinant of surgical outcomes, we examined national Medicare data from patients undergoing CABG. Methods and Results-Among Medicare beneficiaries who underwent CABG between 2008 and 2011, we mapped relationships between all physicians who treated them during their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 33 publications
(28 reference statements)
1
46
0
Order By: Relevance
“…As reported previously, implementation resulted in a significant reduction in length of stay, surgical site infections, and variable direct costs, as well as improvement in the patient experience. [9][10][11] Designation of operating room teams Before the implementation of the ERAS program, anesthesia providers (attending anesthesiologist and anesthesia resident or certified registered nurse anesthetist [CRNA]) were assigned ad hoc to colorectal surgical cases by a central anesthesiologist scheduler. Providers were selected from the entire pool of clinical providers assigned to a particular clinical day.…”
Section: Methods Enhanced Recovery After Surgery Program Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported previously, implementation resulted in a significant reduction in length of stay, surgical site infections, and variable direct costs, as well as improvement in the patient experience. [9][10][11] Designation of operating room teams Before the implementation of the ERAS program, anesthesia providers (attending anesthesiologist and anesthesia resident or certified registered nurse anesthetist [CRNA]) were assigned ad hoc to colorectal surgical cases by a central anesthesiologist scheduler. Providers were selected from the entire pool of clinical providers assigned to a particular clinical day.…”
Section: Methods Enhanced Recovery After Surgery Program Descriptionmentioning
confidence: 99%
“…At least one group found that improved teamworkdas captured by a network measure of provider overlap with patientsdled to better outcomes after coronary artery bypass grafting. 9 In this light, our group sought to better understand the potential impact of ERAS programs on teamwork through the use of social network analysis on a recently implemented ERAS for colorectal surgery program. Our hypothesis was that creating OR teams through the identification of surgical, anesthesia, and nursing leadership coupled with recruitment of designated ERAS providers across the perioperative environment would lead to both improvements in metrics of teamwork, as well as surgical outcomes.…”
mentioning
confidence: 99%
“…Within each health system, we recorded an interaction between physicians if they billed for services for the same beneficiary around that beneficiary's CABG episode. 21 We mapped networks separately for each year and health system. Patients undergoing surgery at the same health system but in different years, or in the same year but at different health systems, experience different networks.…”
Section: Mapping Physician Networkmentioning
confidence: 99%
“…These relationships, analyzed using social network measures, are a product of formal and informal information sharing [13,14], organizational affiliations [15,16], and care coordination [2,8]. Physician shared patient network structurebased in part on their referral patterns-is impacted by insurance type [17,18], patient clinical characteristics [19], socioeconomic characteristics [17,[20][21][22], and organizations [4,15,23].…”
Section: Introductionmentioning
confidence: 99%